Computational outlook on the ribosome as an entropy trap - Monajemi, H.; Wan Abdullah, W.A.T.; Zain, Sharifuddin Md (2011)
Recent progress in the study of transition structure of peptide bond formation indicates that ribosome acts as a water trap. However, considering experimental approaches, it is hard to overlook the role of ribosomal bases in catalyzing the reaction by substrate stabilization. In this study, we employ ab initio quantum chemistry methods to calculate the transition structure of the peptide bond formation in the absence of ribosomal bases. This will allow us to compare the transition structure in the process with the ones obtained computationally in the presence of ribosomal bases, and also the reaction rate with the experimental results. To save calculation time this study was carried out using short fragments of the A and P site aminoacyl-tRNAs. Based on our observation, the absence of ribosome results in a more favorable enthalpy but a less favorable entropy. Overall, the lower rate of reaction compared to that in the ribosomal environment indicates the role of ribosomal bases in catalyzing the reaction 'entropically'. © 2011 Elsevier B.V.